BMAA in cycad-feeding Lepidoptera: defensive sequestration or bioaccumulation? - Whitaker, Melissa R. L.; Banack, Sandra Anne; Mescher, Mark C.; Cox, Paul Alan; De Moraes, Consuelo M. (Frontiers in Ecology and Evolution, 2023)
Many herbivorous Lepidoptera accumulate plant toxins within their own tissues as a defensive strategy. Pioneering research in this area was conducted by Miriam Rothschild and Deane Bowers, who showed that the cycad-feeding butterfly Eumaeus atal} sequester the toxic plant compound cycasin and thereby deter vertebrate and invertebrate predators. The current study focuses on another cycad compound, B-methylamino-L-alanine (BMAA), that is known to accumulate in the tissues of insects and other herbivores, and which has been shown to have neurotoxic effects in humans. Chemical analyses revealed that BMAA accumulates in both immature and adult tissues of E. atala, as well as adult tissues of another cycad-feeding lepidopteran, Seirarctia echo. However, the distribution of BMAA across life stages and tissues of did not conform to patterns predicted for defensive sequestration, and subsequent behavioral experiments with ants showed that these invertebrate predators were not deterred by BMAA. Our results suggest that high levels of BMAA in the tissues of cycad-feeding insects likely reflect passive bioaccumulation rather than defensive sequestration. Combined with the previous work by Rothschild and Bowers, these results provide an example in which two different plant toxins accumulate within the tissues of a single herbivore species via different mechanisms and with different implications for ecology and evolution. They thereby lay the groundwork for further investigation into the processes underlying active sequestration and non-adaptive bioaccumulation.